Establishment and Characterization of a Novel Dedifferentiated Chondrosarcoma Cell Line DDCS2 - Xiaoyang Li (SAGE Publishing, 2021)
Background The dedifferentiated variant of chondrosarcoma is highly aggressive and carries an especially grim prognosis. While chemotherapeutics has failed to benefit patients with dedifferentiated chondrosarcoma significantly, preclinical chemosensitivity studies have been limited by a scarcity of available cell lines. There is, therefore, an urgent need to expand the pool of available cell lines. Methods We report the establishment of a novel dedifferentiated chondrosarcoma cell line DDCS2, which we isolated from the primary tumor specimen of a 60-year-old male patient. We characterized its short tandem repeat (STR) DNA profile, growth potential, antigenic markers, chemosensitivity, and oncogenic spheroid and colony-forming capacity. Results DDCS2 showed a spindle to polygonal shape and an approximate 60-hour doubling time. STR DNA profiling revealed a unique genomic identity not matching any existing cancer cell lines within the ATCC, JCRB, or DSMZ databases. There was no detectable contamination with another cell type. Western blot and immunofluorescence assays were consistent with a mesenchymal origin, and our MTT assay revealed relative resistance to conventional chemotherapeutics, which is typical of a dedifferentiated chondrosarcoma. Under ex vivo three-dimensional (3D) culture conditions, the DDCS2 cells produced spheroid patterns similar to the well-established CS-1 and SW1353 chondrosarcoma cell lines. Conclusion Our findings confirm DDCS2 is a novel model for dedifferentiated chondrosarcoma and therefore adds to the limited pool of current cell lines urgently needed to investigate the chemoresistance within this deadly cancer.